2013
DOI: 10.7860/jcdr/2013/4673.2799
|View full text |Cite
|
Sign up to set email alerts
|

The Patients’ Adherence and Adverse Drug Reactions (ADRs) which are Caused by Helicobacter Pylori Eradication Regimens

Abstract: Background: Helicobacter pylori is a major cause of upper gastrointestinal disorders. The eradication of H. pylori has been recommended for the treatment of different gastrointestinal diseases. Notwithstanding, a combination therapy is needed for Helicobacter pylori eradication, but using these medications can be the cause, the incidence risk of patients' adherence to treatment regimens reduction and probably increase risk of Adverse Drug Reactions (ADRS), so, it is seem that evaluation the out come of combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
4
10
0
Order By: Relevance
“…VAP remains a serious complication amongst critical care patients in any healthcare setting and its incidence has been found to be highly variable not only amongst hospitals, but also in different ICUs in the same hospital. The infection rates seen in the present study were comparable to the figures of 35.1 and 37 per cent in two different studies from India 17 18 . The VAP rate per 1000 ventilator days is a commonly used parameter worldwide, and although its rate was quite low in the USA (4.4) 4 , in various other countries, it was found to be high in the range of 13-51 per 1000 ventilator days 5 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…VAP remains a serious complication amongst critical care patients in any healthcare setting and its incidence has been found to be highly variable not only amongst hospitals, but also in different ICUs in the same hospital. The infection rates seen in the present study were comparable to the figures of 35.1 and 37 per cent in two different studies from India 17 18 . The VAP rate per 1000 ventilator days is a commonly used parameter worldwide, and although its rate was quite low in the USA (4.4) 4 , in various other countries, it was found to be high in the range of 13-51 per 1000 ventilator days 5 .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the Gram-negative bacilli were the principal isolates, and Pseudomonas spp., non-fermenters and Klebsiella spp. were the most common pathogens with almost similar proportion of frequency, and these findings were corroborated by other Indian studies 17 25 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, most studies performed in China revealed that the compliance during H pylori eradication is unpleasant in clinical practice . A prospective study conducted by Abbasinazari et al reported that while regimen type was not relative to patients’ adherence, the frequency of dosing and numbers of medications affected the adherence to treatment. In the present study, the SMRE induced an increased number of patients taking more than 90% of prescribed drugs (84.8% vs 72.8%, P = 0.011), while the number of patients taking <60% of pills were similar in two groups (3.4% vs 2.1%, P = 0.780).…”
Section: Discussionmentioning
confidence: 99%
“…For HP infection, clinical triple therapy is commonly used. [ 10 ] However, because of the poor compliance of patients, [ 11 ] emerging resistant HP strains [ 9 , 12 14 ] and adverse drug reactions, [ 15 17 ] the clinical eradication rate of HP has decreased to an unacceptable low level, [ 18 ] which lead to recurrence frequently. [ 19 , 20 ] The long course of the disease needs to take medicine for a long time, causing great psychological pressure [ 21 , 22 ] to the patient and increasing substantial healthcare costs, which cause significant reductions in patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%